1996
DOI: 10.1086/177411
|View full text |Cite
|
Sign up to set email alerts
|

The Soft and Medium-Energy X-Ray Variability of NGC 5548: A Reanalysis of EXOSAT Observations

Abstract: We present a detailed cross-correlation (CCF) and power spectrum re-analysis of the X-ray light curves of the bright Seyfert 1 galaxy NGC5548 obtained with EXOSAT. The 0.05-2 keV and 1-4 keV light curves are cross-correlated with the 1-9 keV and 4-9 keV light curves respectively. We discuss how spurious time lags can be introduced by systematic effects related to detector swapping as well as the switching on and off of the instruments. We also find strong evidence that one of the ME detectors was not working n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…CURRENTLY THE BEST MODEL Given that viscous heating cannot be the emission process of the rapidly variable optical-UV continuum, the best alternative, suggested by the X-ray variations, is reprocessing. Simultaneity and proportionality on time scales of weeks to months between the medium energy X-ray flux and optical-UV flux have been observed in several AGN (NGC 4151: Perola et al 1986, Warwick et al 1996NGC 5548: Clavel et al 1992, Tagliaferri et al 1996. This is readily explained by a model in which the optical-UV flux is emitted by an optically thick dense medium irradiated by a nearby variable central X-ray source (Collin-Souffrin 1991, Krolik et al 1991, Nandra et al 1991, Molendi et al 1992, Haardt & Maraschi 1993, Rokaki et al 1993, Petrucci & Henri 1997; this dense medium could be the accretion disk.…”
Section: Simultaneity In the Uv Soft- And Hard-x-ray Ranges: Reprocmentioning
confidence: 95%
“…CURRENTLY THE BEST MODEL Given that viscous heating cannot be the emission process of the rapidly variable optical-UV continuum, the best alternative, suggested by the X-ray variations, is reprocessing. Simultaneity and proportionality on time scales of weeks to months between the medium energy X-ray flux and optical-UV flux have been observed in several AGN (NGC 4151: Perola et al 1986, Warwick et al 1996NGC 5548: Clavel et al 1992, Tagliaferri et al 1996. This is readily explained by a model in which the optical-UV flux is emitted by an optically thick dense medium irradiated by a nearby variable central X-ray source (Collin-Souffrin 1991, Krolik et al 1991, Nandra et al 1991, Molendi et al 1992, Haardt & Maraschi 1993, Rokaki et al 1993, Petrucci & Henri 1997; this dense medium could be the accretion disk.…”
Section: Simultaneity In the Uv Soft- And Hard-x-ray Ranges: Reprocmentioning
confidence: 95%
“…It is also difficult to constrain the significance of possible QPOs due to power spectra effects (Vaughan & Uttley 2005b). EXOSAT data of NGC 5548 were reported to have a significant period (Papadakis & Lawrence 1993), but Tagliaferri et al (1996) later showed that the significance of the candidate QPO was lower than previously reported once the uncertainties in modeling the spectrum were taken into consideration.…”
Section: Introductionmentioning
confidence: 91%
“…, with the most famous case being NGC 6814 (Mittaz & Branduardi-Raymont 1989;Done et al 1992). One case has been disputed (Tagliaferri et al 1996) and the the periodicity in NGC 6814 has been refuted decisively (Madejski et al 1993). There are remaining claims in NGC 4051 (Papadakis & Lawrence 1995), RX J0437.4-4711 ( Halpern & Marshall 1996) and IRAS 18325-5926 (Iwasawa et al 1998).…”
Section: Periodicitiesmentioning
confidence: 99%